WLE/IWMI research findings on water and energy use in lift irrigated areas have impacted water policies in Uzbekistan, potentially applicable to over two million hectares - CGIAR Research Program on Water, Land and Ecosystems (2020)
WLE/IWMI research findings demonstrated that substantial water and energy savings could be achieved by adopting more efficient irrigation technologies in the lift irrigated areas of Uzbekistan. Researchers engaged with decision makers and recommended that the government shift subsidies from energy to water saving technologies. This recommendation has been adopted in a state program on water saving technologies covering 450,000 hectares in 2021.